Epidemiology And Clinical Pattern Of Atopic Dermatitis In 100 Children seen In A City Hospital - Dhar Sandipan; Mandal Bisweswar; Ghosh Apurba (Wolters Kluwer Medknow Publications, 2002)
A topic desmatitis is a fairly common disorder in the paediatric population. One hundred children were evaluated for epidemiology and clinical pattern with reference to age, age of onset, history of atopy, seasonal variation, type, distribution and extent of eczema etc. The results were tabulated, analysed and compared with data from previous studies. Findings such as onset at a very young age, a male preponderance, summer aggravation, facial dermatitis in preschool children, more acute presentation less disease severity and other regional variations are discussed.